Intrathecal Hydrocortisone in the Treatment of Tuberculous Meningitis (Preliminary Report) - Harsoyo N.; Moeljono S. Trastotenojo; Soejono Soejono; Dedy Abubakar; Indra Warman (Indonesian Pediatric Society, 1976)
A trial on the treatment of tuberculous meningitis with intrathecal hydrocortisone, beside INH, PAS, and Streptomycin, performed at the Dr. Kariadi General Hospital in October 1972, is reported. Eighteen patients were treated, giving good results; 5.6% mortality were noted. A great number of complications of optic nerve atrophy (61.1 %) were found and 22.2% with early atrophy recovered. The results are better compared with those of Choremis et al. (1957) who found a mortality of 13.7% among 29 patients with tuberculous meningitis treated in the same way, except P.A.S.